Critical Spaces: European and U.S. Institutions for Outer Space. Issue 1 (2nd January 2022) - Brandenburg, Matthea; Lieberman, Sarah
ABSTRACT: Space is an area characterized by geopolitical positioning the past seven decades. Over that time, agencies and institutions have developed, charged with the task of ensuring the safe usage and exploration of orbits. In the United States, NASA is synonymous with space travel, and in Europe there is the European Space Agency in conjunction with the European Union and state actors all funded at a lower level than NASA and charged with fewer responsibilities. In this paper, we ask why these institutions developed in such different ways and to such different extents? Using the concept of historical institutionalism, we examine the history of each and discuss the path-dependent nature of the institutions in question. Broadening the discussion, we note that while institutional formation engenders a profound impact on the current activity of each agency, geopolitical factors cannot be disregarded, and power structures within the global system are of a greater impact than historical institutionalism.